Measuring trust and commitment in collective actions: Evidence from farmers’ marketing organizations in rural Ethiopia - Tadesse, Getaw; Tesfahun Kassie, Girma (Emerald Publishing Limited, 2017)
The purpose of this paper is to explore the theoretical and empirical possibility of measuring trust and commitment in collective actions.The study employs choice experiments to estimate trust implicitly as opposed to the common practice of measuring trust explicitly. Several experiments were conducted to assess members’ level of trust and commitment to marketing cooperatives in rural Ethiopia.The results of the study indicate that significant number of farmers do not yet have trust in their organization and fellow members in both absolute and relative terms. The probability of trust increases when members actively participate in cooperative governance, are less diverse, stay longer in the cooperative, and when cooperatives are older. The authors also learnt that both trust and commitment have indeed improved the performance of farmers’ market organizations. Trust in cooperative is asymmetrically sensitive to incentives and disincentives.The study implied that research efforts attempting to estimate trust in collective action shall use an implicit measurement and consider the sensitivity of trust to relativeness, incentives and types of transactions.The findings of this study showed that rural organizations that are established with external help, such as agricultural cooperatives in Africa, seem to struggle to earn the trust of their current and potential members. This implies that given the effectiveness and persistence of informal rural organizations emerged through mutual trust, cooperatives must be organized either through informal ways as trust-based organizations or based on cooperative business principles of voluntarism and independence.This paper employs the behaviorally appealing choice experiment approach to capture the different aspects of trust such as relativism, sensitivity of trust to incentive and types of transactions in smallholder producers’ organizations.